Trust in Medical Professionals Moderates Depression in Hong Kong during COVID-19 - Lai, Daniel W. L.; Jin, Jiahui; Yan, Elsie; Lee, Vincent W. P. (Depression and Anxiety, 2023)
Objectives. Given the continuing COVID-19 pandemic and the associated prevention and control measures implemented, the psychological burden brought by the pandemic on citizens is expected to increase. This study is aimed at exploring the predictors of depressive symptoms among Hong Kong people during the epidemic, as well as factors that could potentially alleviate the negative effects of the epidemic. Methods. The third wave follow-up survey (December 2021 to January 2022) from a longitudinal prospective survey study conducted in Hong Kong was used for a cross-sectional analysis. The participants (n=803) are adults aged 18 and above in Hong Kong. Logistic and linear regression were performed to test the predictors and moderating effects, respectively, with depression as the outcome variable. Results. With minimized confounding effects of demographic variables, higher levels of concern about infection, experience with COVID-19 infection and previous epidemics, hassles, and trust in authority increased the odds of being depressed, while a higher level of trust in medical professionals reduced the odds of depression. Moreover, greater trust in medical professionals, as a moderator, lessened the positive associations between the levels of depression and hassles and concern about infection. Conclusions. Even though the threats of COVID-19 seem to have lowered, this study shows that a few factors associated with the pandemic continue to threaten people’s mental health. However, developing greater trust in medical experts may be an effective way to relieve psychological burden.